In-Vitro Screening of Some Germplasms of Vigna under Salinity Condition (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: in-vitro; salinity; tolerant; susceptible Bangladesh j. genet. biotechnol. 6 (1&2): 37-40, 2005 (June & December)